From Digital Technology to Healthy Habits: Interdisciplinary Foundations for Developing Training Programs for a Healthy Lifestyle Among Children - Dolenc, Kosta; Fošnarič, Samo (Revija za elementarno izobraževanje, 2025)
This article explores the impact of digital technology on children’s development, focussing on the physical, cognitive, and emotional domains. The introduction emphasises the benefits of digital tools for education and language acquisition, but also points out the associated risks such as physical inactivity, sleep disturbances and mental health problems. A rigorous methodological approach ensures the inclusion of high-quality data, while subsequent sections explore key themes, including the interplay between screen time, physical activity, and diet. The conclusion emphasises interdisciplinary interventions, including the ZŽS project framework, which integrates technology, health, and environmental responsibility. This approach aims to promote healthier lifestyle choices.
Keywords: digital technology, child development, mental health, physical activity.